Effect of Different Catalysts on the Production Rate of Biogas from Banana Leaves - P Jena, Shakti; P Patra, Priyanka; Nanda, Sagar; K Acharya, Saroj (International Journal of Engineering and Technology, 2018)
In this study, the effect of metal oxide nanoparticles (NPs) such as titanium oxide (TiO2) and aluminum oxide (Al2O3) mixed with urea (2% by dry mass of the leaves) added to 500 ml of sewage water samples on production of biogas and was compared with the results of pure sewage water as base effluent. The observations revealed that sewage water with urea alone (S+U) showed better performance in the production of biogas and methane content than pure sewage water and NPs mixed inoculums. Maximum methane yield content was found in case of S+U effluent as recorded to be 65.28% in 38 days. While methane content of pure sewage was found to be 54.46 % in 46 days and in case of TiO2 added effluent methane yield was found to be 59.18 % in 38 days and in case of Al2O3 added effluent it was recorded to be 54.88% in 42 days.
Keywords: Anaerobic digestion; biogas; methane; microbes; nanoparticles.